Re-entry at the point of entry. - Glover, Kit; Bumby, Kurt (Corrections Today, 2001)
Part of a special section on the administration of juvenile justice in the U.S. The writers discuss the work of the Missouri Division of Youth Services (DYS). They note that an underlying philosophy within the DYS is the importance of planning for the eventual release of youths from the very beginning. They explain that the DYS maintains a commitment to safeguarding Missouri citizens by offering individualized and comprehensive needs-based services that ultimately allow youths to successfully return to their families and communities. They describe some of the services and approaches that DYS offers, focusing on the agency's transitional and aftercare services.